1989
DOI: 10.1016/0035-9203(89)90642-1
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of drug resistance in Trypanosoma cruzi and Leishmania donovani by verapamil

Abstract: Following previous studies of verapamil reversal of chloroquine resistance in malaria and multi-drug resistance in cancer cells, the effect of verapamil was investigated on nifurtimox-resistant Trypanosoma cruzi in vitro and antimony-resistant Leishmania donovani in vitro and in vivo. Verapamil alone was not active against either parasite, but in combination with nifurtimox it reversed the drug resistance of T. cruzi and in combination with sodium stibogluconate reversed the drug resistance of L. donovani.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
29
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 4 publications
4
29
0
2
Order By: Relevance
“…Verapamil had been reported earlier to inhibit the efflux of drugs through ABC transporters (20). Similar inhibitory effects of verapamil had also been found in Trypanosoma and laboratory-derived resistant L. donovani isolates (43). In our study, we have found that verapamil (an inhibitor of MDR1) partially reverses the AmB resistance phenotype, a result which has been demonstrated by partial inhibition of AmB efflux (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Verapamil had been reported earlier to inhibit the efflux of drugs through ABC transporters (20). Similar inhibitory effects of verapamil had also been found in Trypanosoma and laboratory-derived resistant L. donovani isolates (43). In our study, we have found that verapamil (an inhibitor of MDR1) partially reverses the AmB resistance phenotype, a result which has been demonstrated by partial inhibition of AmB efflux (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Earlier studies have demonstrated that if AmB-induced cell damage is related to generation of ROS (41), the cell's resistance to damage might depend on its ability to decompose them efficiently (4, 7). It had earlier been reported that kinetoplastids detoxify hydroperoxides mainly by the tryparedoxin pathway (39,43). To investigate the involvement of the tryparedoxin cascade in ROS scavenging, the expression levels of different thiol metabolic pathway genes were investigated in both resistant and sensitive parasites.…”
Section: Discussionmentioning
confidence: 99%
“…As has been noted with first-line drugs, verapamil might reduce the macrophage-induced drug tolerance to bedaquiline (4). As in other organisms (17,18), verapamil may prevent the emergence of further drug resistance and thus preserve the activity of bedaquiline. Given the extremely low MIC values achieved with the combination of bedaquiline and verapamil, a drug regimen containing these two agents may be highly effective for the treatment of both drug-resistant and drug-susceptible M. tuberculosis strains.…”
mentioning
confidence: 73%
“…In addition, it has been shown that macrophage-induced M. tuberculosis tolerance persists after lysis of macrophages; this mechanism is potentially important for bacterial tolerance in the necrotic caseum, where bacilli may be extracellular (4). In addition to its potential role as an antimycobacterial agent, verapamil has been previously shown to block the acquisition of drug resistance in Trypanosoma cruzi and Leishmania donovani (30), and chloroquine resistance in Plasmodium falciparum (31). Verapamil was recently shown to restore susceptibility toward first-line anti-TB drugs in mice infected with a multidrug-resistant M. tuberculosis strain (9).…”
Section: Discussionmentioning
confidence: 99%